Consistent assignment of the vibrations of symmetric and asymmetric para-disubstituted benzene molecules - Andrejeva, Anna; Gardner, Adrian M.; Tuttle, William D.; Wright, Timothy G. (Elsevier, 2016)
We give a description of the phenyl-ring-localized vibrational modes of the ground states of the para-disubstituted benzene molecules including both symmetric and asymmetric cases. In line with others, we quickly conclude that the use of Wilson mode labels is misleading and ambiguous; we conclude the same regarding the related ones of Varsányi. Instead we label the modes consistently based upon the Mulliken (Herzberg) method for the modes of para-difluorobenzene (pDFB). Since we wish the labelling scheme to cover both symmetrically- and asymmetrically-substituted molecules, we apply the Mulliken labelling under C2v symmetry. By studying the variation of the vibrational wavenumbers with mass of the substituent, we are able to identify the corresponding modes across a wide range of molecules and hence provide consistent assignments. Particularly interesting are pairs of vibrations that evolve from in- and out-of-phase motions in pDFB to more localized modes in asymmetric molecules. We consider the para isomers of the following: the symmetric dihalobenzenes, xylene, hydroquinone, the asymmetric dihalobenzenes, halotoluenes, halophenols and cresol.